Review of urological cancers in Damaturu, Nigeria - Tela, Usman M.; Adamu, Adamu I.; Abubakar, Babagana M.; Abubakar, Abdulkadir; Dogo, Hassan M. (International Journal of Research in Medical Sciences, 2021)
Background: Urological cancers (UC) remain a major global burden and a significant cause of high morbidity and mortality. In other to plan and tackle this burden, there is need to audit the pattern of these malignancies in our locality which is currently lacking. Hence, the objectives of our study were to describe the histological pattern, frequency and demographic characteristics of urological cancers seen in Damaturu. Methods: The reports of all the urological specimens that were histologically diagnosed as malignant between November 2017 to October 2019 in the histopathology department of Yobe state university teaching hospital, were analyzed. The department keeps newly established cancer registry for the state. Results: Fifty-five UC were diagnosed, with male to female ratio of 13.8:1. These UC constitute 34.1% of the 161 urological specimens assessed and 26.4% of all types of medical cancers diagnosed in the period of study. Prostate cancer dominates the UC (41; 73.8%), followed by bladder cancers (11; 19.8%) and the remaining kidney, penis and testicular cancers (1; 1.8%) each. Conclusions: Urological cancers are very common in our region, particularly prostate cancers in which majority were poorly differentiated. This report though analyzed few cancers, the proportion of UC is high. Urothelial cancer of the bladder is now more frequent than squamous cell carcinoma. This study can serve as basis for future epidemiologic studies targeting at the risk factors, awareness and prevention of UC.